Odpowiedź :
a)
[tex]2 \sqrt{3} + 3 \sqrt{3} - \sqrt{3} = 4 \sqrt{3} [/tex]
b)
[tex]3 \sqrt{5} - 4 \sqrt{5} + \sqrt{5} = 0[/tex]
c)
[tex]4 \sqrt{2} + 5 \sqrt{2} = 9 \sqrt{5} [/tex]
d)
[tex]5 \sqrt{7} - 3 \sqrt{7} = 2 \sqrt{7} [/tex]
e)
[tex] \sqrt{11} - 5 \sqrt{11} + 7 \sqrt{11} = 3 \sqrt{11} [/tex]
f)
[tex]6 \sqrt{6} + 2 \sqrt{6} - 7 \sqrt{6} = \sqrt{6} [/tex]
g)
[tex]4 \sqrt{8} - 5 \sqrt{8} + 6 \sqrt{8} = 5 \sqrt{8} = 5 \sqrt{4 \times 2} = 10 \sqrt{2} [/tex]
h)
[tex] - \sqrt{3} - 3 \sqrt{3} + 10 \sqrt{3} = 6 \sqrt{3} [/tex]
i)
[tex]7 \sqrt{15} - 2 \sqrt{15} = 5 \sqrt{15} [/tex]
Myślę że pomogłem ;)
Odpowiedź:
a) [tex]2\sqrt{3}+3\sqrt{3} -\sqrt{3}[/tex] = [tex]4\sqrt{3}[/tex]
b) [tex]3\sqrt{5} - 4\sqrt{5} +\sqrt{5} =0[/tex]
c) [tex]4\sqrt{2} +5\sqrt{2} =9\sqrt{2}[/tex]
d) [tex]5\sqrt{7} -3\sqrt{7} =2\sqrt{7}[/tex]
e) [tex]\sqrt{11} -5\sqrt{11} +7\sqrt{11} =3\sqrt{11}[/tex]
f) [tex]6\sqrt{6} +2\sqrt{6} -7\sqrt{6} =\sqrt{6}[/tex]
g) [tex]4\sqrt{8} -5\sqrt{8} +6\sqrt{8} =5\sqrt{8}[/tex]
h) [tex]-\sqrt{3} -3\sqrt{3} +10\sqrt{3} =6\sqrt{3}[/tex]
i) [tex]7\sqrt{15} -2\sqrt{15} =5\sqrt{15}[/tex]
Szczegółowe wyjaśnienie: